Electroosmotic flows and electromigrations during electrokonetic processing of tropical residual soil - Ahmad, Kamarudin; Kassim, Khairul Anuar; Taha, Mohd. Raihan (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)
Saturated soft soils can be strengthened by several methods such as dewatering or adding suitable chemicals. Introduction of chemicals through electrokinetic (EK) process to strengthen a residual soil was investigated. The results of chemical tests on an elecrokinetically-treated tropical residual soil are presented. The chemical substances used as electrolytes in the experiments were aluminum chloride (Al), calcium chloride (Ca) and phosphoric acid (PA) in addition to distilled water (DW). Four different opened-anode and opened-cathode electrokinetic systems were employed in this study, namely DW-DW, Al-DW, Ca-DW and DW-PA. A constant voltage of 30 V was applied for 168 hours to each of the opened-anode and opened-cathode configuration system. It was observed that the quantities and directions of electroosmotic flows were dependent upon the types of electrolyte. The chemical contents of the treated samples were position dependent and influenced by both the electrolyte types and electroosmotic flows.